Recording conceptual art : early interviews with Barry, Huebler, Kaltenbach, LeWitt, Morris, Oppenheim, Siegelaub, Smithson, Weiner - Barry, Robert, 1936-; Alberro, Alexander; Norvell, Patsy, 1942- (Berkeley : University of California Press, 2001)
Recording Conceptual Art features a highly provocative series of previously unpublished interviews conducted in early 1969 with some of the most dynamic, daring, and innovative artists of the tumultuous 1960s. The nine individuals--eight artists and one art dealer--are now known as major contributors to Conceptual art.
Preliminaries; LIST OF ILLUSTRATIONS; ACKNOWLEDGMENTS; PREFACE; INTRODUCTION; INTRODUCTION TO ELEVEN INTERVIEWS; NOTE ON THE INTERVIEWS; Dennis Oppenheim; Seth Siegelaub; Robert Morris; Stephen Kaltenbach; Robert Barry; Lawrence Weiner; Sol LeWitt; Robert Smithson; Douglas Huebler; INDEX.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Barry, Robert -- 1936-; Huebler, Douglas -- 1924-1997; Kaltenbach, Stephen J. -- 1940-; LeWitt, Sol -- 1928-2007; Morris, Robert -- 1931-2018; Oppenheim, Dennis -- 1938-2011; Siegelaub, Seth -- 1941-2013; Smithson, Robert -- 1938-1973; Weiner, Lawrence -- 1942-2021; Conceptual art -- United States; Artists -- United States -- Interviews; Art conceptuel -- États-Unis.; Artistes -- États-Unis -- Entretiens; ART -- Conceptual; Artists; Conceptual art; United States; Interview; Concept-art; Künstler; USA; Conceptuele kunst; Verenigde Staten; Art conceptuel -- États-Unis.; interviews; Interviews; Interviews (vorm); Interviews; Interviews